Enhanced gene transfection efficiency by low-dose 25 kDa polyethylenimine by the assistance of 1.8 kDa polyethylenimine. (1st January 2018) - Zhang, Hui; Chen, Zhiyi; Du, Meng; Li, Yue; Chen, Yuhao
Abstract: Gene therapy is a promising strategy for treatments of various diseases. Efficient and safe introduction of therapeutic genes into targeted cells is essential to realize functions of the genes. High-molecular-weight polyethylenimines (HMW PEIs) including 25 kDa branched PEI and 22 kDa linear PEI are widely used for in vitro gene transfection. However, high-gene transfection efficiency is usually accompanied with high cytotoxicity, which hampers their further clinical study. On the contrary, low-molecular-weight polyethylenimines (LMW PEIs) such as 1.8 kDa PEI and 800 Da PEI show good biocompatibility but their applications are limited by the poor DNA condensation capability. In this study, we find that 1.8 kDa PEI, but not 800 Da PEI combined with low-dose 25 kDa PEI could significantly promote gene transfection with low cytotoxicity. Plasmids encoding enhanced green fluorescence protein (EGFP) were delivered by the combined PEI and gene transfection efficiency was evaluated by microscopic observation and flow cytometry. Parameters including concentrations of 25 kDa PEI and 1.8 kDa PEI and preparation ways were further optimized. This study presents an efficient and safe combined PEI-based non-viral gene delivery strategy with potential for in vivo applications.